Penguatan Hak Penguasaan Desa Adat atas Tanah PKD di Desa Cempaga - I Nyoman Sutama; I Gusti Bagus Suryawan; I. B. Komang Suarka (Universitas Warmadewa, 2023)
The purpose of community service in Cempaga village is to increase villagers' understanding of the existence of customary land, especially PKD land. The issues raised were the existence of tenure rights over customary land and efforts to strengthen customary village tenure rights over PKD land in the Cempaga customary village. The service method is carried out through counseling and assistance to indigenous village residents. With the enactment of the ATR/BPN ministerial decree number 276 / KEP – 19.2 / X / 2017 it is stated that customary villages are the subject of communal rights in land registration. This provision is strengthened by the enactment of Ministerial Regulation ATR/BPN number 6 of 2018 concerning complete systematic land registration (PTSL) which stipulates that customary land must be registered. Referring to this regulation, PKD land in Cempaga village can be registered in the name of Cempaga customary village. This provision was strengthened by the PERDA of the Province of Bali concerning customary villages which states that customary land is registered in the name of a customary village, so that the position of a customary village in the control of customary land is very strong.